The SEED Wellness Model: A Workplace Approach to Address Wellbeing Needs of Healthcare Staff During Crisis and Beyond - Pai, Padmini; Olcoń, Katarzyna; Allan, Julaine; Knezevic, Andrea; Mackay, Maria; Keevers, Lynne; Fox, Mim; Hadley, Anne Marie (Frontiers in Health Services, 2022)
1 Workplace wellness has gained new meaning and significance in the healthcare workforce in the face of the COVID-19 pandemic. Healthcare workers across the world have carried the burden of responding to the public health crisis by having to work under new pressures and constantly changing environments, take on additional shifts, risk their own health and lives, and cope with the ongoing psychological and emotional strain. The purpose of this paper is to articulate a workplace wellness model applied across hospitals in the Illawarra Shoalhaven Local Health District, a regional area in New South Wales, Australia. The description of the development, components, and lessons learned from the SEED Wellness Model illustrates one possible solution about how to provide better care for the staff thus not only preventing staff burnout and turnover, but also creating lasting organizational benefits. The detailed model description can assist in developing a larger and more rigorous evidence-base to improve staff wellness in healthcare settings, both within Australia and internationally.